Effects of β-like cell autotransplantation through hepatic arterial intervention on diabetic dogs. (3rd July 2016) - Mu, Yongxu; Hao, Zhiming; He, Junfeng; Yan, Ruiqiang; Liu, Haiyan; Zhang, Lei; Liu, Heming; Hu, Xiaoyan; Li, Qiming
Abstract : Exogenous insulin and EGFP genes were transduced into bone marrow mesenchymal stem cells of beagle dogs using the retroviral vector pMSCV to prepare β-like cells. These cells were autotransplanted into the liver of diabetic dogs through hepatic arterial intervention, and physiological indices before and after transplantation were monitored. Autotransplantation of β-like cells significantly improved blood sugar, insulin levels, and body mass of diabetic dogs ( P < 0.01) continuously for over 80 weeks. Since the liver function remained normal and no tumors formed, this method was determined to be reliable and safe. Intrahepatic autotransplantation of β-like cells had long-term, reliable, and safe therapeutic effects on diabetic dogs.